Optimization of Polystyrene Biodegradation using Response Surface Methodology (RSM) Measured by Simple Colorimetric Method - K. Meng, T.; Y.Y. Beng, D.; S. Mohd Kassim, A.; H. A. Razak, A.; A. Mohd Fauzi, N. (International Journal of Engineering and Technology, 2019)
Nearly 280 kilotons of polystyrene (PS) waste being discarded yearly in Malaysia. Banning usage of PS food packaging aims to minimize this â€œwhite pollutionâ€. However, the existing PS waste volume remains the same despite the termination of PS production. Therefore, this study has investigated the optimization of biodegradation of PS using isolated strain Bacillus aryabhattai as an alternative solution to the biodegradation of recalcitrant plastic. The effect of pH and temperature as independent variables were studied at three levels each (pH: 6, 7.5 and 9, temperature: 25 Â°C, 35 Â°C and 45 Â°C) under the designation by three level-factorial and analysed using response surface methodology (RSM) by Design Expert Version 10.0. The biodegradation activity of Bacillus aryabhattai was quantified using simple colorimetric method. Bacillus aryabhattai was inoculated on the dye PS-film and incubated under designed conditions. As a result of biodegradation, the entrapped methylene blue dye was released and measured photometrically. Optimum conditions for the highest reading of blue dye absorbance were obtained at pH 9 and temperature of 25ÂºC with the desirability of 75.9%. This study provides significant information on the biodegradation activity of Bacillus aryabhattai for future research that can be applied in waste management.Â